2015
DOI: 10.1055/s-0035-1565208
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in Primary Aldosteronism

Abstract: In recent years, an increasing number of studies have revealed deleterious effects of aldosterone via the mineralocorticoid receptor (MR). Especially in patients with primary aldosteronism (PA) a significant higher estimated risk of developing cardiovascular comorbidities and comortalities compared to essential hypertensives was reported. As diabetes mellitus and the metabolic syndrome are one of the major contributors to cardiovascular morbidity and mortality their connection to aldosterone excess became a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 75 publications
(194 reference statements)
4
21
0
Order By: Relevance
“…Hypokalemia was associated with lower insulin secretion from pancreatic β-cells in an in vitro study; therefore, the presence of hypokalemia in PA might confound investigations of the link between PA and glucose status [11,16,39]. Therefore, we also separately analyzed PA patients according to hypokalemia status and adjusted for hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hypokalemia was associated with lower insulin secretion from pancreatic β-cells in an in vitro study; therefore, the presence of hypokalemia in PA might confound investigations of the link between PA and glucose status [11,16,39]. Therefore, we also separately analyzed PA patients according to hypokalemia status and adjusted for hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Only few data from human studies are available regarding the molecular mechanisms underlying the impairment in glucose metabolism in PA [26]. However, many studies conducted in animal and cell models suggest that aldosterone impairs glucose metabolism at several levels, including insulin secretion, hepatic glucose production and uptake, and glucose diffusion and uptake into insulin-sensitive tissues [5][6][7][8][9][10][11][12][13][14]. In the present study, the subgroup analysis (comprising~28% of the study subjects) showed that HOMA-β was lower in PA patients than in matched controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations